A new nonlinear constitutive model of CSG. Issue 1 (2nd January 2022) - Feng, Xinjun; Zhang, Fangfang; Guo, Lixia; Zhong, Ling
ABSTRACT: Cemented sand and gravel (CSG) is a kind of green building material that has emerged in recent years. The cement content has a great impact on the deformation characteristics of CSG, but the current constitutive models cannot reflect this problem. Based on the previous research results, this paper depicted the volume strain and shear strain of CSG, established a nonlinear constitutive model of CSG, and finally verified the new constitutive model with experimental data. Results showed that the model could well simulate the deformation characteristics of the CSG with cement content of more than 40 kg/m 3, and the entire stress–strain relationship was basically consistent with the experimental value, reflecting the adaptability and superiority of the nonlinear constitutive model of CSG.